Tuning the luminescence behaviors of a chloroplatinum(ii) complex by component exchanges of dynamic acylhydrazone bonds. Issue 1 (11th November 2014) - Liang, Jianjun; Huang, Huanting; He, Lipeng; Liu, Nijuan; Chen, Yanhuan; Bu, Weifeng
Abstract : The exchange reactions of dynamic acylhydrazone bonds with acylhydrazine or aldehyde lead to controllable emissions of a cationic chloroplatinum(ii ) complex in water. Abstract : A cationic chloroplatinum(ii ) complex was found to show remarkable luminescence enhancement upon self-assembly with tripodal dynamic acylhydrazone-bridged sulfonates in water. The successive exchange reactions with acylhydrazine or aldehyde resulted in a controllable decrease in the luminescence intensities.